A KNOWLEDGE BASED SYSTEM: AN EXPERT DIRECTORY FOR E&P BUSINESS - Kasim, Fatihah (Universiti Teknologi Petronas, 2006)
The purpose of this report is to present the initial proposal of the author's final year project entitled "A Knowledge Based System: Expert Directory for E&P Business". In these present days, knowledge has become a key resource. Many top organizations have changed their way of doing business in the past and develop the foundations of characteristics for success. The birth of knowledge management grew from recognition of the difficulty of dealing with the complexity in finding the right information and dealing with the complexity in achieving the demands of the sophisticated customer. Awareness came to organizations when they started to the realize the value of knowledge and information, followed by searching for the ways to create, store, integrate, share and make available the right knowledge to the right people at the right time. This is allwhat the system is all about, to make it easier for users to find what they need in one system; to cut short the time for finding the needed resource as well as to add efficiency in finishing any projects within organization. The first part, ofthis report will discuss on background study, problem statement, and the objectives and the scope ofthe project. To support the research, a literature review and theory will be included in the picture showing the path ofprior research and how existing studies in various areas are linked to this project. The methodology in completing this project will be based on incremental development and extreme programming. The conclusion summarizes the proposed idea and findings to inform readers on author's current phase on project development.